Sharks : nature's perfect hunter - Flood, Joe (Illustrator) (Science comics (First Second (Firm)), 2018)
Provides a comprehensive guide to sharks using a graphic novel format. Describes the biology, behavior, diet, and proliferation of sharks along with dispelling common shark-related myths. Includes a glossary, a shark family tree, and a list of phrases one can use instead of "shark attack."